MiSeq raw sequences (Run 2) of the V4 region 16S rRNA gene from the spleens of 348 murinae from Senegal and 26 positive and negative controls (part 2 to 3) - Galan, Maxime; Razzauti, Maria; Bard, Emilie; Bernard, Maria; Brouat, Carine; Charbonnel, Nathalie; Dehne-Garcia, Alexandre; Loiseau, Anne; Tatard, Caroline; Tamisier, Lucie; Vayssier-Taussat, Muriel; Vignes, Hélène; et al. (Dryad Digital Repository, 2016)
This ZIP file contains the FASTQ files of the paired-end reads (R1: reads 1; R2: reads 2) produced for each individual in duplicate using the MiSeq platform (Run 2). The 746 multiplexed PCR products were indexed using both forward and reverse indices. The list of the 355 multiplexed samples and the 26 positive and negative controls are provided in the following XLSX file titled: Information concerning the samples multiplexed in the MiSeq Run 1 & 2.